What Is the Role of AI in Alzheimer's Disease Diagnosis? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2015)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder that affects millions of people worldwide. Early and accurate diagnosis is crucial for m...
Keywords: AI in Neurology; Alzheimer's; Disease; Diagnosis; Artificial Intelligence; Machine Learning